Labor and professions market for young professionals in the face of economic crisis: challenges and solutions - E. . Kuzmin (Высшее образование в России)
The author analyzes the impact of the economic crisis on the labor market for youngprofessionals, which have just graduated from universities. The article asserts the need for state support of this category in job placing. The problem of unemployment among young professionals and the imbalance between the economy needs and the current education system is discussed.